2003
DOI: 10.1007/s00415-003-1039-7
|View full text |Cite
|
Sign up to set email alerts
|

The degree of depression in Hamilton rating scale is correlated with the density of presynaptic serotonin transporters in 23 patients with Wilson's disease

Abstract: We conclude that depression in patients with Wilson's disease is correlated with alterations of serotonergic neurotransmission in the thalamus-hypothalamus region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 19 publications
3
29
0
Order By: Relevance
“…Using [ 123 I] -CIT SPECT, it was found that the severity of depression was negatively correlated with the SERT availability in the thalamus/hypothalamus region [637,638]. In the midbrain, WD patients showed significantly lower SERT availability, compared to healthy controls, regardless of whether depression was evident or not [148].…”
Section: Serotonin Transporter Imaging In Neurological Diseasesmentioning
confidence: 96%
“…Using [ 123 I] -CIT SPECT, it was found that the severity of depression was negatively correlated with the SERT availability in the thalamus/hypothalamus region [637,638]. In the midbrain, WD patients showed significantly lower SERT availability, compared to healthy controls, regardless of whether depression was evident or not [148].…”
Section: Serotonin Transporter Imaging In Neurological Diseasesmentioning
confidence: 96%
“…Furthermore, reduced 5-HTT availability, as putatively indexed by the 5-HTTLPR short allele, has been associated with mood disturbances, including major depression (especially in the context of environmental stressors; Caspi et al, 2003;Eley et al, 2004;Kaufman et al, 2004;Kendler, Kuhn, Vittum, Prescott, & Riley, 2005;Malison et al, 1998), as well as with more severe depression and anxiety in various psychiatric disorders (Eggers et al, 2003;Heinz et al, 2002;Willeit et al, 2000).…”
Section: Serotonin-transporter Genetic Variation and Individual Diffementioning
confidence: 99%
“…Decreased serotonin transporter densities (SERT) have been recorded from the brains of depressed patients [1,2], which have also been reported to normalise during psychotherapy [3,4]. A few studies have also revealed altered levels of dopamine transmission in major depression [5,6].…”
Section: Introductionmentioning
confidence: 99%